DALUWARSA DALAM KUHP DAN FIQH JINAYAH - Hanif Azhar (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2018)
This research is motivated by the prescription in the Indonesia Criminal Code (KUHP) which is became one of the causes of a prosecutor cannot prosecute and execute a sentence against a criminal offender. A concept that was initially unknown in Islamic criminal law (fiqh jinayah). The purpose of this study is to compare the concepts of prescription in the Indonesia Criminal Code and Islamic jurisprudence. This study uses a library research method with a comparative approach. The conclusion of this study is that the Indonesia Criminal Code the prescription applies to all criminal acts at the level of prosecution and the execution of penalties. On another side the prescription in Islamic criminal law can only be applied to takzir crime at the same level, namely prosecution and executing sentences.